HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KENAIKAN BERAT BADAN BAYI DI DESA BANJAREJO KECAMATAN DAGANGAN KABUPATEN MADIUN - Arfan, Nurul Azmi; Nuzula, Rizka Firdausi; Sandi, Devi Fitria; Uzair, Salma (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2026)
Exclusive breastfeeding is an essential determinant of infant nutritional status during the first six months of life. This study aims to determine the relationship between exclusive breastfeeding and infant weight gain in Banjarejo Village, Dagangan District, Madiun Regency. A retrospective cross-sectional design was used with 38 respondents selected through stratified random sampling. Data were collected using questionnaires and KMS growth charts and analyzed with the Chi-square test. The results showed that 78.9% of mothers provided exclusive breastfeeding, 57.9% of infants experienced weight gain, and 66.7% of exclusively breastfed infants had appropriate weight gain. There was a significant relationship between exclusive breastfeeding and infant weight gain (p = 0.034). Keywords: exclusive breastfeeding, infant growth, weight gain, nutrition